2021
DOI: 10.3389/fonc.2021.752642
|View full text |Cite
|
Sign up to set email alerts
|

GPI Is a Prognostic Biomarker and Correlates With Immune Infiltrates in Lung Adenocarcinoma

Abstract: BackgroundGlucose-6-phosphate isomerase (GPI) plays an important role in glycolysis and gluconeogenesis. However, the role of GPI in lung adenocarcinoma (LUAD) remains unclear.MethodsAll original data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and integrated via R 3.2.2. GPI expression was explored with TCGA, GEO, and Oncomine databases. Immunohistochemistry staining was used to analyze GPI expression in clinical specimens. The correlations between GPI and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
3
28
0
Order By: Relevance
“…In addition, our study indicated that the expression level of GPI was significantly related to the tumor stage, ER or PR state, and age. Similarly, Han's study (10) pointed out that the expression level of GPI in LUAD was significantly higher than that in paracarcinoma tissues. Rose (21) reported that serum GPI was often elevated in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, our study indicated that the expression level of GPI was significantly related to the tumor stage, ER or PR state, and age. Similarly, Han's study (10) pointed out that the expression level of GPI in LUAD was significantly higher than that in paracarcinoma tissues. Rose (21) reported that serum GPI was often elevated in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 90%
“…The previous reports have indicated that GPI is significantly related to tumor metastasis and poor prognosis of some tumors (10)(11)(12). In this study, database analysis showed that the expression levels of GPI in many human tumors were frequently altered.…”
Section: Discussionmentioning
confidence: 99%
“…It may function as a cytokine and angiogenic factor. The aberrant expression of GPI has been involved in the development and progression of several cancers, such as adrenal cortical carcinoma, lung adenocarcinoma, and malignant melanoma, possibly by influencing immune cell infiltration [ 36 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPI plays a crucial part in the process of glycolysis and gluconeogenesis ( 24 , 25 ). Earlier studies showed that GPI could be used as a prognostic biomarker in cancer because of its important work in the cell cycle ( 26 , 27 ). In our study, GPI was a risk gene because a higher expression was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%